2009
DOI: 10.1007/s10561-009-9127-2
|View full text |Cite
|
Sign up to set email alerts
|

What tissue bankers should know about the use of allograft meniscus in orthopaedics

Abstract: The menisci of the knee are two crescent shaped cartilage shock absorbers sitting between the femur and the tibia, which act as load sharers and shock absorbers. Loss of a meniscus leads to a significant increase in the risk of developing arthritis in the knee. Replacement of a missing meniscus with allograft tissue can reduce symptoms and may potentially reduce the risk of future arthritis. Meniscal allograft transplantation is a complex surgical procedure with many outstanding issues, including 'what techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…In such cases, attempts can be made to replace the damaged tissue with a functional substitute to restore function of normal meniscus. Although meniscus transplantation using allografts can achieve encouraging clinical results [ 10 - 14 ], concerns over many factors – tissue availability, mismatch of size and shape of graft and host, immunogenicity, disease transmission, and deterioration of the allograft’s mechanical properties after implantation – still persist [ 15 - 17 ]. To circumvent these problems, synthetic meniscus substitutes have been tested.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, attempts can be made to replace the damaged tissue with a functional substitute to restore function of normal meniscus. Although meniscus transplantation using allografts can achieve encouraging clinical results [ 10 - 14 ], concerns over many factors – tissue availability, mismatch of size and shape of graft and host, immunogenicity, disease transmission, and deterioration of the allograft’s mechanical properties after implantation – still persist [ 15 - 17 ]. To circumvent these problems, synthetic meniscus substitutes have been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Each tissue bank uses different proprietary cleansing methods; some preservation methods have historically increased failure rates. 3,10 …”
mentioning
confidence: 99%
“…One reason for the lack of significance found in some of our analyses might be the small sample size in the present study, combined with the number of risk factors examined, which could have led to a lack of statistical power. The methods in the present study were better controlled compared to some previous research: only fresh-frozen meniscal allografts (which are biologically and mechanically superior to other forms of preservation [41]) were used, and these were all sourced from a single provider, and a single onesurgeon technique was used. Previous authors have either not reported their allograft sources [38,42] or have used multiple providers with different preservation techniques [13].…”
Section: Discussionmentioning
confidence: 99%